Given that x + x 1 = 2 1 + 5 , find the value of x 2 0 0 0 + x 2 0 0 0 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How come your solution is in English, but the problem is in Spanish??? Are you bilingual??? Wow !!
@Matthew Yu I changed the problem to english, so that most of the users could understand it.
This problem is a duplicate of Matt's problem .
Log in to reply
No, it is in Spanish
@milind prabhu you should not say that it is a duplicate, the problem-poster might have not known that this problem has already appeared on the site.
Exactly,Milind!
Let ϕ = 2 1 + 5 . One can easily check that this number, also known as the golden ratio, satisfies ϕ 2 − ϕ − 1 = 0 . Substituting ϕ = x + x 1 we obtain:
0 = x 2 − x + 1 − x 1 + x 2 1 = x 2 1 ( x 4 − x 3 + x 2 − x + 1 ) = x 2 ( x + 1 ) x 5 + 1 .
We see that x 5 = − 1 , meaning that
x 2 0 0 0 + x 2 0 0 0 1 = ( − 1 ) 4 0 0 + ( − 1 ) 4 0 0 1 = 1 + 1 = 2 .
x + x 1 = 2 1 + 5 m u l t i p l y b y x . x 2 − ( 2 1 + 5 ) x + 1 = 0 ∴ x = 2 2 1 + 5 ± ( 2 1 + 5 ) 2 − 4 x = 2 2 1 + 5 ± 4 6 + 2 5 − 4 , m u l t i p l y b y 2 2 x = 4 1 + 5 ± 4 2 5 − 1 0 n o t e t h a t 2 5 − 1 0 < 0 s o x s h o u l d b e w r i t t e n a s : x = 4 1 + 5 ± 4 i 1 0 − 2 5 w e o b t a i n t h e m o d u l u s a n d a r g u m e n t o f t h i s c o m p l e x n u m b e r . r = ( 4 1 + 5 ) 2 + ( 4 1 0 − 2 5 ) 2 = 1 6 6 + 2 5 + 1 6 1 0 − 2 5 = 1 θ = tan − 1 1 + 5 1 0 − 2 5 = 3 6 ∴ x = c o s ( 3 6 ) ± i s i n ( 3 6 ) . a c c o r d i n g t o d e − m o i v r e ′ s t h e o r e m : x 2 0 0 0 = 1 2 0 0 0 ( c o s ( 3 6 × 2 0 0 0 ) ± i s i n ( 3 6 × 2 0 0 0 ) ) = c o s ( 2 0 0 × 2 π ) ± i s i n ( 2 0 0 × 2 π ) = c o s ( 2 π ) ± i s i n ( 2 π ) = 1 + 0 = 1 ∴ x 2 0 0 0 + x 2 0 0 0 1 = 1 + 1 1 = 2
same way! .
Solving the given equation as a quadratic equation you find that the solutions of x is complex. Hence z n + z n 1 = 2 cos n θ is applicable (which is a formula derived from de Moirve's theorem). Using the given equation you can solve this for n = 1 and find θ . 2 cos θ = 2 1 + 5 ∴ θ = 5 π . Hence you can plug this value back into z n + z n 1 = 2 cos n θ for n = 2 0 0 0 to get x 2 0 0 0 + x 2 0 0 0 1 = 2 cos 2 0 0 0 5 π = 2 .
simple ,, let x=cos a + i sin a and then u have 1/x= cos a - i sin a (i am assuming modulus of x as 1 here ) then we have 2 cos a = 1+root5/2 so which clearly tells a is 36 degrees, now write down x in complex number form and use demouvires theorem to get the value of Re(e^(i2000a))= 1 ,,, hence adding the real parts of x and 1/x ,, we get 2
Let x=cos∆+isin∆ =>∆ is 36° so GE =2cos2000∆ which is nothing but 2
Problem Loading...
Note Loading...
Set Loading...
Notice the golden ratio. When applicable, geometry is very powerful in solving algebra problems. Consider a triangle A B C with ∠ B = ∠ C = 5 2 π and ∠ A = 5 π .
In △ A B C notice that A B / B C is the golden ratio. Using the law of sines B C A B = sin 5 π sin 5 2 π = sin 5 π 2 sin 5 π cos 5 π = 2 cos 5 π
let x = e i θ , x 1 = e − i θ , x + x 1 = 2 cos 5 π
x 2 0 0 0 + x 2 0 0 0 1 = 2 cos 5 2 0 0 0 π = 2 cos 4 0 0 π = 2